Beyond the Prompt: What Data Do AI Chatbots Truly Collect? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The rapid integration of AI chatbots—powered by Large Language Models LLMs—into professional and personal life has fundamentally altered how we interact with...
Keywords: Digital Health; Healthcare Data; Medical Ethics